Impacto da pesca sobre a mortalidade de tartarugas-verdes (Chelonia mydas) na costa do Espírito Santo - Uzai, Letícia Maria Silva (2016)
Due to human activities, green turtles (Chelonia mydas) have suffered population reduction, especially of juvenile specimens. This study aimed to determine the number of deaths recorded in C. mydas in Espírito Santo beaches due to the fishery (directly and indirectly) in the years 2013-2014, as well as associate the biometric features in these animals. Data were obtained by retrospective survey of registration records and autopsy C. mydas from running aground. Descriptive statistics were performed and the nonparametric Spearman correlation at 5% probability. The beaches with higher mortality were: Suá beach and Curva da Jurema beach, in Vitória; Boa Vista do Sul beach, in Marataízes; Porto Velho beach, in Anchieta; Piúma beach in Piúma and Itaipava beach in Itapemirim. In 76% (222/293) the primary cause of death was classified as direct impact and in 24% (71/293) as indirect. It was found that 568 Chelonia mydas they had died during the study period and the impact fishing has been responsible for the death of 52% (293/568) of animals. Of these it was found that 87% (254/293) were female and 13% (39/293) males, with an average weight of 5.95 kg (± 2.83), curved carapace length 37.86 cm (± 7.43) and curved carapace width average of 34.68 cm (± 6.83). A good body condition was recorded in 53% (154/293) of animals and the season with higher mortality was the winter with 29% (85/293). There was statistically significance of the fishing impact with the weight and the fishing impact with the body condition. We conclude that in the years 2013 to 2014 the beaches with the highest mortality rate in C. mydas were those with greater representation in the fishing industry and tourism in the state. Most affected subjects were female, juvenile and those with good body condition, moreover, the fishing impact was negatively correlated with the smallest weight and with poor body condition.